Dielectric relaxation and electro-optic response in nano-ceria dispersed ferroelectric liquid crystal nanocomposites: effect of structural deformation and lattice straining. Issue 38 (30th April 2015) - Goel, Puja; Arora, Manju
<x xml:space="preserve">Abstract</x> The current investigations deal with the effect of concentration of CeO2 nanoparticles (NPs) on physical properties of ferroelectric liquid crystal.